PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Pasaribu, Yokebet; Simbolon, Naeklan; Mailani, Elvi; Rozi, Fahrur; Sembiring, Masta Marselina (Universitas Negeri Medan, 2024)
This research aims to determine the influence of the make a match type cooperative learning model in class IV of SD Negeri 091496 on student learning outcomes in equivalent fraction material. This type of research is a pre-experiment, one group pretest-posttest. The sample used in this research was saturated sampling, namely class IV because there were 26 students. Data collection techniques are observation, interviews, tests/evaluations and documentation. The analysis technique uses the t-test formula. The results of the research show that there is an influence of the make a match type cooperative learning model on student learning outcomes in equivalent fraction material in class IV SDN 091496 Pematang Tanah Jawa. Based on the test, the pretest results obtained an average of 44.87 and a variance of 382.361 with the highest score of 86.7 and the lowest score of 20 with a sample size of 26 students. Meanwhile, the posttest results obtained an average of 75.64 with a variance of 131.417 with the highest score of 100 and the lowest score of 53.3. The results of hypothesis testing show that t_count is 16.603 with t_table 1.708. It can be seen that t_count > t_table is 16.603 > 1.708 which means H_o is rejected and H_a is accepted . Based on the results of data analysis and statistical tests as well as discussion, it can be concluded that there is a significant influence of the make a match type cooperative learning model on student learning outcomes in grade IV fraction material at SDN 091496 Pematang Tanah Jawa.